FSH regulates RA signaling to commit spermatogonia into differentiation pathway and meiosis - Maryam Khanehzad; Roya Abbaszadeh; Marzieh Holakuyee; Mohammad Hossein Modarressi; Seyed Mehdi Nourashrafeddin (BMC, 2021)
Abstract Background Spermatogenesis is a complex process that is controlled by interactions between germ cells and somatic cells. The commitment of undifferentiated spermatogonia to differentiating spermatogonia and normal spermatogenesis requires the action of gonadotropins. Additionally, numerous studies revealed the role of retinoic acid signaling in induction of germ cell differentiation and meiosis entry. Main text Recent studies have shown that expression of several RA signaling molecules including Rdh10, Aldh1a2, Crabp1/2 are influenced by changes in gonadotropin levels. Components of signaling pathways that are regulated by FSH signaling such as GDNF, Sohlh1/2, c-Kit, DMRT, BMP4 and NRGs along with transcription factors that are important for proliferation and differentiation of spermatogonia are also affected by retinoic acid signaling. Conclusion According to all studies that demonstrate the interface between FSH and RA signaling, we suggest that RA may trigger spermatogonia differentiation and initiation of meiosis through regulation by FSH signaling in testis. Therefore, to the best of our knowledge, this is the first time that the correlation between FSH and RA signaling in spermatogenesis is highlighted.